1992
DOI: 10.1152/ajplung.1992.263.5.l526
|View full text |Cite
|
Sign up to set email alerts
|

Differential systemic and intrapulmonary TNF-alpha production in Candida sepsis during immunosuppression

Abstract: Candida albicans (CA) increasingly causes septic shock, acute lung injury, and multiple organ damage during immunosuppression-related neutropenia. However, the effects of neutrophil (PMN) depletion on induction of tumor necrosis factor-alpha (TNF) by CA and its potential mediation of Candida septic shock are unknown. We hypothesized that reduced CA uptake by circulating PMNs during cyclophosphamide (CY)-related neutropenia sensitizes to TNF-mediated shock from enhanced cytokine production after phagocytosis by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…Although the study did not elucidate the mechanism of SP-A's impact, it is possible to assume that the binding of SP-A to TLR may alter the interaction of Candida to the cell surface receptor, resulting in the down-regulation of proinflammatory cytokine release. Intrapulmonary TNF-␣ production causes local inflammatory tissue injury and lethal septic shock in Candida sepsis during immunosuppression (11). Taken together with this study, these works give credence to the important physiological role of SP-A in regulating pulmonary inflammation elicited by fungi.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Although the study did not elucidate the mechanism of SP-A's impact, it is possible to assume that the binding of SP-A to TLR may alter the interaction of Candida to the cell surface receptor, resulting in the down-regulation of proinflammatory cytokine release. Intrapulmonary TNF-␣ production causes local inflammatory tissue injury and lethal septic shock in Candida sepsis during immunosuppression (11). Taken together with this study, these works give credence to the important physiological role of SP-A in regulating pulmonary inflammation elicited by fungi.…”
Section: Discussionsupporting
confidence: 75%
“…Intratracheal challenge of zymosan has been shown to induce pulmonary inflammation in animal models (10). Intrapulmonary TNF-␣ production causes lung tissue injury and severe pulmonary inflammation in disseminated candidemia under immunosuppressive conditions (11).…”
mentioning
confidence: 99%
“…However, the behavior of AMs during disseminated candidiasis is insufficiently elucidated. Lechner et al (15) reported that tumor necrosis factor (TNF) levels in BALF of neutropenic animals with candidemia are elevated, whereas TNF levels in serum remain low, even at death. They assumed that impaired clearance of yeast-phase C. albicans by circulating polymorphonuclear cells leads to extensive yeast mycelium transformation in the pulmonary vasculature, hyphal outgrowth from pulmonary capillaries, and increased TNF production by AMs in response to hyphal elements in the distal air spaces.…”
Section: Discussionmentioning
confidence: 99%
“…Another blood sample (0.6 ml) for the measurement of plasma TNFcx levels was obtained at 90 min after the injection of LPS, a time point at which the rise in TNFoE after LPS is maximal (Lechner et al, 1993). The amounts of TNFaE in the plasma were measured by an enzyme linked immunoadsorbent assay (ELISA) as previously described (Lechner et al, 1992). …”
Section: Measurement Ofplasma Levels Of Tumour Necrosis Factor-cc (Tnfc)mentioning
confidence: 99%